Peter Brears: All the King’s Cooks. The Tudor Kitchens of King Henry VIII at Hampton Court Palace - Jaine, Tom (Petits Propos Culinaires, 2012)
Peter Brears: All the King’s Cooks. The Tudor Kitchens of King Henry VIII at Hampton Court Palace: Souvenir Press, 2011, 192pp., paperback, £15.00.